Shariah Hospitals in Indonesia: Bridging Islamic Values and Healthcare Management (Universitas Muhammadiyah Yogyakarta, 2025)
This systematic review summarizes evidence related to the implementation of Sharia-compliant hospitals in Indonesia. The researchers conducted a search on Google Scholar, SAGE Journals, and PubMed (2019–2024; English/Bahasa Indonesia) utilizing Boolean and MeSH terms, excluding non-Sharia contexts, general healthcare without Sharia content, and non-empirical materials. Eligible studies consisted of empirical articles that examined Sharia-compliant hospital management, service processes, or patient-reported experiences. Supplementary searches included citation chasing and hand-searching; targeted checks in Scopus and Web of Science revealed no further eligible records. Out of 3,583 records screened, 18 studies fulfilled the inclusion criteria. The review adhered to PRISMA 2020 guidelines, incorporating dual independent screening and quality appraisal suitable for the design. Numerous studies have shown that enhanced Sharia compliance, through certification, halal-compliant pharmacy and nutrition, gender-sensitive services, and organized spiritual support, correlates with increased patient satisfaction and trust. Compliance varied among facilities. System-level constraints comprised restricted availability of halal medicine, inadequate implementation of standard operating procedures, limitations in staffing for gender-sensitive care, and inconsistent oversight. Future research ought to employ comparable measures, quasi-experimental or multicenter designs, and cross-country benchmarks to evaluate the compliance and satisfaction pathway and guide policy development. This synthesis sets a policy and management-ready agenda: standardized compliance metrics and common satisfaction instruments; strengthened halal-medicine supply chains and workforce planning; and transparent, feedback-linked complaint handling to drive continuous improvement.